2023
DOI: 10.3389/fonc.2023.1171837
|View full text |Cite
|
Sign up to set email alerts
|

Multi-clinical index classifier combined with AI algorithm model to predict the prognosis of gallbladder cancer

Abstract: ObjectivesIt is significant to develop effective prognostic strategies and techniques for improving the survival rate of gallbladder carcinoma (GBC). We aim to develop the prediction model from multi-clinical indicators combined artificial intelligence (AI) algorithm for the prognosis of GBC.MethodsA total of 122 patients with GBC from January 2015 to December 2019 were collected in this study. Based on the analysis of correlation, relative risk, receiver operator characteristic curve, and importance by AI alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Its low sensitivity is not suitable for MRD detection, but with the rise of AI image recognition technology, the problem of cell morphology inspection about the order of magnitude is expected to be solved to a certain extent. According to the results of the study, it was also found that when patients obtained CR before harvesting, the possibility of their samples being contaminated by tumor cells was significantly reduced [14][15]. However, for patients who obtained VGPR or PR before harvesting, there was no statistical significance in the positive proportion of samples being contaminated by tumor cells between the two groups, and even if patients obtained CR before harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Its low sensitivity is not suitable for MRD detection, but with the rise of AI image recognition technology, the problem of cell morphology inspection about the order of magnitude is expected to be solved to a certain extent. According to the results of the study, it was also found that when patients obtained CR before harvesting, the possibility of their samples being contaminated by tumor cells was significantly reduced [14][15]. However, for patients who obtained VGPR or PR before harvesting, there was no statistical significance in the positive proportion of samples being contaminated by tumor cells between the two groups, and even if patients obtained CR before harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AH<0: the intermolecular hydrogen bond prevents the water molecules from forming a hydration layer around the polymer chain, and the freedom of water molecules is reduced, so the -TAS of the system is >0. When the temperature is low, the -TAS value is small, the system AG<0, and the polymer-water system is a homogeneous solution [12]. When the temperature increases, the molecular kinetic energy increases, the hydrogen bond stability between the hydrophilic groups on the polymer and the water molecules decreases, the hydrogen bond interaction weakens, the thermal effect decreases, and the AH value decreases.…”
Section: Reversible Temperature-sensitive Transition Of Pnipammentioning
confidence: 99%
“…Additionally, PD-L1 and NY-ESO1 are indicative markers for immunotherapy[ 150 , 174 ]. The predictive factors for favorable prognosis are shown in Table 3 [ 34 , 112 , 156 , 169 , 170 ].…”
Section: Prognosismentioning
confidence: 99%
“…A prediction model of prognosis that is based on multiple clinical indications, in combination with artificial intelligence algorithms, has been recently developed[ 34 ].…”
Section: Introductionmentioning
confidence: 99%